Capsaicin: a spicy way in liver disease - Li, Shenghao; Hao, Liyuan; Yu, Fei; Li, Na; Deng, Jiali; Zhang, Junli; Xiong, Shuai; Hu, Xiaoyu (Frontiers in Pharmacology, 2024)
The incidence of liver disease continues to rise, encompassing a spectrum from simple steatosis or non-alcoholic fatty liver disease (NAFLD) to non-alcoholic steatohepatitis (NASH), cirrhosis and liver cancer. Dietary habits in individuals with liver disease may significantly impact the treatment and prevention of these conditions. This article examines the role of chili peppers, a common dietary component, in this context, focusing on capsaicin, the active ingredient in chili peppers. Capsaicin is an agonist of the transient receptor potential vanilloid subfamily 1 (TRPV1) and has been shown to exert protective effects on liver diseases, including liver injury, NAFLD, liver fibrosis and liver cancer. These protective effects are attributed to capsaicin’s anti-oxidant, anti-inflammatory, anti-steatosis and anti-fibrosis effects. This article reviewed the different molecular mechanisms of the protective effect of capsaicin on liver diseases.